Reitox national reporting to EMCDDA on drugs and drug addiction, 2020 - L Van Baelen; Jérôme Antoine; L. Gremeaux; Peter Blanckaert; E Plettinckx (2021)
Yearly contribution to the European Monitor Center for Drugs and Drug Addiction (EMCDDA) in collecting, analysing and disseminating information on drugs and drug addiction in Europe. In order to fulfil its mandate, the EMCDDA relies on the collaboration with the European information network (Reitox), consisting of all national drug observatories in the EU Member state plus Turkey, Norway and the European Commission. Each of these Reitox National Focal Points collects information and produces comparable and scientifically sound data on the national drug situation. Up to 2014, Reitox national reports were provided to the EMCDDA on an annual basis to feed the monitoring of the situation across Europe. Since 2015, the EMCDDA changed strategies concerning the transfer of the national drug-related information, which allows the Centre to better address the needs for information of European and National Stakeholders. The newly implemented reporting tool does no result in a standalone document that can be published for national objectives. Nevertheless, the annual reporting & related information is certainly at hand and anyone can receive tailored information upon request to the Belgian national focal point at Sciensano. The annual reporting comprises of 10 Chapters: Chapter 1: Drug Policy Chapter 2: Legal Framework Chapter 3: Drug use in (the) (sub)population(s) Chapter 4: Prevention Chapter 5: Treatment Chapter 6: Best Practice Chapter 7: Harms and harm reduction Chapter 8: The drug market and crime Chapter 9: Prison Chapter 10: research